The impact of lipid-lowering medications on coronary artery plaque characteristics - Vishnu Priya Pulipati; Francis J. Alenghat (Elsevier, 2021)
Atherosclerosis is the predominant cause of coronary artery disease. The last several decades have witnessed significant advances in lipid-lowering therapies, which comprise a central component of atherosclerotic cardiovascular disease prevention. In addition to cardiovascular risk reduction with dyslipidemia management, some lipid-based therapies show promise at the level of the atherosclerotic plaque itself through mechanisms governing lipid accumulation, plaque stability, local inflammation, endothelial dysfunction, and thrombogenicity. The capacity of lipid-lowering therapies to modify atherosclerotic plaque burden, size, composition, and vulnerability should correlate with their ability to reduce disease progression. This review discusses plaque characteristics, diagnostic modalities to evaluate these characteristics, and how they are altered by current and emerging lipid-lowering therapies, all in human coronary artery disease.